Assédio moral no trabalho em Luanda, Angola e na Região Metropolitana de São Paulo, Brasil - Matamba, Jacinto (2021)
Mobbing at work is a theme that has gained visibility in society. It is characterized by the repetition, for long periods of time of hostile behaviors, developed by a superior or co-worker against other workers. It acquires different denominations in different countries and for different authors. Considering the impact that abusive behaviors can generate on the mental health of workers and the few studies conducted in both contexts, the present research, characterized as exploratory, has the general objective of assessing the expression of mobbing at work in the city of Luanda, Angola and in the Metropolitan Region (RMSP) of São Paulo, Brazil. The approach to the problem becomes pertinent, because a better knowledge of this reality will enable us to act preventively or act more effectively when facing the mobbing in organizations. The present study aims to identify the expression of mobbing directed at workers in the city of Luanda, Angola and in RMSP, Brazil, using the Portuguese Mobbing Scale (EMP, 2005). A sociodemographic questionnaire containing personal information was used, age, gender, marital status and length of service, along with the scale. The results indicated that in Luanda and the RMSP, moral harassment at work is expressed in a similar way, but to a lesser extent in Angola. Cultural issues allow us to understand the differences as well as the observed regularities, which constitute in different societies at the confluence of organizational culture with power relations